Oxygen transport to tissue XXXII - LaManna, Joseph C.; Puchowicz, Michelle A.; Xu, Kui.; Harrison, David K.; Bruley, Duane F.; SpringerLink (Online service). (New York [N.Y.] Springer Science+Business Media, 2011)
Based on the 2009 proceedings of the 37th annual ISOTT conference, this volume covers all aspects of oxygen delivery to tissue, everything from near infrared spectroscopy, tumor biology, angiogenesis and mitochondrial metabolism to systems modeling, gas transport, hypoxic adaptation and exercise physiology. Special emphasis is placed on methods of oxygen measurement in living tissue and application of these technologies to understanding physiological and biological bases for pathology related to tissue oxygenation. This multidisciplinary volume includes contributions from scientists, engineers, clinicians and mathematicians and is aimed and students and experts from a range of research fields.
Near Infrared Spectroscopy.The Western Reserve, Edward Morley and Oxygen.Analysis of the Changes in the Oxidation of Brain Tissue Cytochrome c Oxidase in Traumatic Brain Injury Patients during Hypercapnoea: A Broadband NIRS Study.Effects of Assuming Constant Optical Scattering on Haemoglobin Concentration Measurements using NIRS during a Valsalva Manoeuvre.Speech Therapy Changes Blood Circulation and Oxygenation in the Brain and Muscle: A Near-Infrared Spectrophotometry Study -- Oxygen Sensors and Measurement.Evaluation of Lithium Naphthalocyanine (LiNc) Microcrystals for Biological EPR Oximetry.Challenges to Intestinal pO2 Measurement Using EPR.Quantification of Systemic Interference in Optical Topography Data during Frontal Lobe and Motor Cortex Activation: An Independent Component Analysis.Measuring Oxygen in Living Tissue: Intravascular, Interstitial and "Tissue" Oxygen Measurements.Cerebral Oxygenation of the Cortex and Striatum following Normobaric Hyperoxia and Mild Hypoxia in Rats by EPR Oximetry Using Multi-Probe Implantable Resonators.31P-MRS Studies of Melanoma Xenograft Metastatic Potential.Modulation of Tumor Hypoxia by Topical Formulations with Vasodilators for Enhancing Therapy -- Blood and Blood Substitutes.MP4, A Vasodilatory PEGylated Hemoglobin.Zymogen Protein C to Prevent Clotting Without Bleeding During Invasive Medical Procedures -- Tumor Biology.Oxygenation Status of Urogenital Tumors.Tumor pO2 as a Surrogate Marker to Identify Therapeutic Window during Metronomic Chemotherapy of 9L Gliomas.Hypoxia-induced Extracellular Acidosis Increases p-glycoprotein activity and chemoresistance in tumors in vivo via p38 signaling pathway.Evidence Against a Major Role for TKTL-1 in Hypoxic and Normoxic Cancer Cells.NMR Metabolic and Physiological Markers of Therapeutic Response.Characterizing Breast Cancer Mouse Xenografts with T1p-MRI: A Preliminary Study.Effect of AEM Energy Applicator Configuration on Magnetic Nanoparticle Mediated Hyperthermia for Breast Cancer.Highly Specific, NIR Fluorescent Contrast Agent with Emission Controlled by Gold Nanoparticle -- Presidential Symposium.Oral Pioglitazone Reduces Infarction Volume and Improves Neurologic Function Following MCAO in Rats -- Angiogenesis.Chronic Mild Hypoxia Ameliorates Chronic Inflammatory Activity in Myelin Oligodendrocyte Glycoprotein (MOG) Peptide Induced Experimental Autoimmune Encephalomyelitis (EAE).Effect of Oxygenation on Stem-Cell Therapy for Myocardial Infarction -- Mitochondrial Metabolism.Regulation of Cytosolic and Mitochondrial Oxidation via Malate-Aspartate Shuttle: An Observation Using Dynamic 13C NMR Spectroscopy.In Vivo Assessment of Oxygen Consumption via Deuterium Magnetic Resonance.Elevated Mitochondrial DNA Copy Number and POL-? Expression but decreased Expression of TFAM in Murine Intestine following Therapeutic Dose Irradiation.Heterogeneity of Mitochondrial Redox State in Premalignant Pancreas in a PTEN Null Transgenic Mouse Model.Potential Application of 17O MRI to Human Ischemic Stroke -- Development.Fetal Cerebral Oxygenation: The Homeostatic Role of Vascular Adaptations to Hypoxic Stress.Impaired Cerebral Autoregulation Using Near-Infrared Spectroscopy and its Relation to Clinical Outcomes in Premature Infants -- Systems Modeling.Variable ATP Yields and Uncoupling of Oxygen Consumption in Human Brain.Interpretation of NMR Spectroscopy Human Brain Data with Multi-Compartment Computational Model of Cerebral Metabolism.Regional Brain Blood Flow in Mouse: Quantitative Measurement Using Single-Pass Radio-Tracer Method and Mathematical Algorithm -- Microcirculation and Wound Healing.Wound Healing in Diabetes: Hemorheological and Microcirculatory Aspects.Modeling O2-dependent Effects of Nitrite Reductase Activity in Blood and Tissue on Coupled NO and O2 Transport around Arterioles.Skin SO2 Measurement Using Visible Lightguide Spectrophotometry in a Black Population: A Feasibility Study.Antioxidant Properties of Quercetin.Antioxidant Properties of Select Radiation Mitigators Based on Semicarbazone and Pyrazole Derivatives of Curcumin -- Gas Transport.Impact of Intracellular Diffusion of Oxygen in Hypoxic Sensing.The Micropores in the Vitteline Layer of the Eggs of the Dragonfly Oligoaeshna Pryeri: A Preliminary Observation from the View Point of Oxygen Uptake -- Hypoxic Adaptation.A Heat-Shock Protein Co-Inducer Treatment Improves Behavioral Performance in Rats Exposed to Hypoxia.Chronic Intermittent Hypoxia-induced Augmented Cardiorespiratory Outflow Mediated by Vasopressin-V1A Receptor Signaling in the Medulla.The Effect of Inspiration of 12% O2 (balance N2) on Cardiac Output, Respiration, Oxygen Saturation and Oxygen Delivery.Sufficient Oxygen Can Be Transported to Resting Skeletal Muscle -- Exercise Physiology.Skeletal Muscle Perfusion and Oxygenation Assessed by Dynamic NMR Imaging and Spectroscopy.Hemoglobin and Myoglobin Contributions to Skeletal Muscle Oxygenation in Response to Exercise.Estimation of Muscle Fatigue Using Surface Electromyography and Near-Infrared Spectroscopy.
Electronic reproduction.
Keywords: Oxygen -- Physiological transport -- Congresses; Tissue respiration -- Congresses; Oxygen consumption -- Physiology -- Congresses; Biological transport -- Physiology -- Congresses; Oxygen -- Metabolism -- Congresses; Electronic books